Pendampingan dan Praktik Penghitungan Waris Sesuai Sanad Syekh Hisyam Kamil pada Guru Pondok PM Sultan Hasanudin Banten - Nita Andriani (Fakultas Dakwah IAIN Jember, 2021)
The distribution of inheritance rights is a natural thing to do for the heir to the heirs who have been left behind. And the distribution of inheritance in Indonesia uses customary law, civil law and Islamic law (Mawaris). And based on the distribution of inheritance law currently in force in Indonesia, there are three parts, namely; 1) the existence of Islamic inheritance law, 2) the existence of customary law, and 3) Burgerlijk Wetboek. So accompanied by Ustadz H. Mardi Hadi Lc, he provided assistance and practice in calculating inheritance in accordance with Sheikh Hisyam Kamil's chain to the teachers of PM Sultan Hasanudin Banten. With this assistance, teachers are the initial foundation for spreading this knowledge in the community. So this study will discuss further how the mentoring and practice of calculating inheritance according to the sanad of Sheikh Hisyam Kamil at the Pondok Guru Sultan Hasanuddin Banten is carried out. In this study using research with a phenomenological approach or qualitative research. Meanwhile, for the validity of the data in this study, the triangulation technique was used. Assistance in training Mawaris/Faraidh for PM Sultan Hasanudin Banten's teachers. The bersanad ends today after approximately 2 months. The sanad was obtained from Sheikh Hisham Kamil Hamid Musa al-Azhari (Egyptian scholar). Following the Daurah of his own book. From the results of interviews conducted on the respondent of the mentoring participants, namely the PM teacher, Sultan Hasanudin Banten, he interpreted the standard of public knowledge about inheritance. In order to spread the knowledge of Mawaris and eliminate the habits of the people who are used to sharing inheritance with customary law. The conclusion from the results of this study is that the community, especially around Banten, needs to get attention from religious leaders and local religious organizations otherwise injustice and inheritance distribution will continue not according to the Shari'a. And this condition will not only be felt in the Banten area but also in other parts of Indonesia.